" تحليل مستوى الإفصاح عن المخاطر في التقارير المالية السنوية للمصارف التجارية الليبية " دراسة تحليلية - البرغثي , وليد إبراهيم محمد (Scientific Journal of University of Benghazi, 2020)
The study aimed to know the level of disclosure of risks in the annual financial reports of commercial banks, and the deductive and inductive approaches were adopted. As for the method of data collection, the study used the method of content analysis for a set of financial indicators and items. The statistical program (SPSS) was used. The study relied on the consolidated financial reports of the banks that Issued by the Central Bank of Libya annually, for a period of (10) years, which starts from 2009 and ends in 2018. The number of banks participating in the study reached (18) banks. Among the most important findings of the study is that all commercial banks disclose at different levels of banking risks, while most banks found not to disclose items related to hedging risks, and also concluded that there are non-material differences in the levels of disclosure between banks and other financial institutions.